Floating Rate Notes and Stakeholder Activities During Zero and Negative Interest Rate Regimes - Juergen Klaus; Eriks Selga; Tony Klein (Queen's University Belfast, Queen's Management School, 2019)
We analyse the impact of stakeholder interactions with the market as a consequence of the negative interest rate regime on the pricing of selected Floating-rate notes (FRNs). The range of reactivity of financial markets and issuers to uncertainty caused by an untested boilerplate term in bond contracts are thoroughly outlined. The subject clause stipulates 'not applicable' as the minimum rate of interest, which raises confusion regarding payment obligations between issuers and investors. This is discussed from a legal perspective. Empirically, we find that markets do—to varying degrees—price stakeholder activities like court decisions, industry association statements, and public positions of sovereigns. In turn, issuers are willing to react to legal risks quickly, if costs of inertia are low. This is reflected also in the significant changes in the FRN issuance structure in the past few years. The announcement of further lower for longer rates in the Euro Area provides evidence that the FRN market appreciates the current protection of negative coupons even under a lower Euribor.
Keywords: K00; 330; Sovereign Bond Markets; Floating Rate Notes; Negative Interest Rates; Legal Uncertainties